Compensation Practices in Forwarding Companies in an Islamic Perspective: Praktik Kompensasi pada Perusahaan Ekpedisi dalam Perspektif Islam - Khoir, Miatul; Haryanto, Rudy (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2024)
This study aims to examine the compensation practices given by the expedition company to its couriers. Secondly, to review the system and practices from an Islamic perspective. This research uses a qualitative method through a phenomenological approach that focuses on the experience and awareness of the subject as a courier. This research was conducted in Sampang for two months, from April to early June. As for data collection through interviews and joint interviews with informants totalling twelve people who work for expedition companies including JNE, J&t, Shopee Express, Anter Aja and Id Express. The results of this study: First, there are differences in compensation practices in expedition companies that are adjusted to company policies. Second, based on the review of the Islamic perspective, there are several companies whose compensation systems and practices are not in accordance with the principles in the Islamic perspective.